Measurements of CP violation in the three-body phase space of charmless B± decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
The charmless three-body decay modes B±→K±π+π−, B±→K±K+K−, B±→π±K+K− and B±→π±π+π− are reconstructed using data, corresponding to an integrated luminosity of 3.0 fb−1, collected by the LHCb detector. The inclusive CP asymmetries of these modes are measured to be ACP(B±→K±π+π−)=+0.025±0.004±0.004±0.007,ACP(B±→K±K+K−)=−0.036±0.004±0.002±0.007,ACP(B±→π±π+π−)=+0.058±0.008±0.009±0.007,ACP(B±→π±K+K−)=−0.123±0.017±0.012±0.007,where the first uncertainty is statistical, the second systematic, and the third is due to the CP asymmetry of the B±→J/ψK± reference mode. The distributions of these asymmetries are also studied as functions of position in the Dalitz plot and suggest contributions from rescattering and resonance interference processes.